2022
DOI: 10.1161/jaha.121.025216
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Veno‐Arterial Extracorporeal Life Support With and Without an Impella or Intra‐Aortic Balloon Pump for Cardiogenic Shock

Abstract: Background Mechanical circulatory support devices, such as the intra‐aortic balloon pump (IABP) and Impella, are often used in patients on veno‐arterial extracorporeal life support (VA‐ECLS) with cardiogenic shock despite limited supporting clinical trial data. Methods and Results Hospitalizations for cardiogenic shock from 2016 to 2018 were identified from the National Inpatient Sample. Trends in the use of VA‐ECLS with and without an IA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…The observed in‐hospital mortality in the patients requiring VA‐ECMO was 46.9% to 58.5% with a decreasing trend, which was almost consistent with those in the previous study. 36 The increase in the use of ECPella was about twice as large as that of Impella (12.8% versus 6.6%), which might be partly due to the expectation of left ventricular unloading. Further investigation is required as to whether left ventricular unloading by the concomitant use of an Impella with VA‐ECMO improves the outcome as compared with that by the concomitant use of an IABP with VA‐ECMO.…”
Section: Discussionmentioning
confidence: 88%
“…The observed in‐hospital mortality in the patients requiring VA‐ECMO was 46.9% to 58.5% with a decreasing trend, which was almost consistent with those in the previous study. 36 The increase in the use of ECPella was about twice as large as that of Impella (12.8% versus 6.6%), which might be partly due to the expectation of left ventricular unloading. Further investigation is required as to whether left ventricular unloading by the concomitant use of an Impella with VA‐ECMO improves the outcome as compared with that by the concomitant use of an IABP with VA‐ECMO.…”
Section: Discussionmentioning
confidence: 88%
“…Another recent single-institution study not included in the meta-analysis reported similar findings. 21 Finally, a recent large “real world” study of the Nationwide Inpatient Sample demonstrated no survival benefits associated with left-sided cardiac unloading 22 ; when subgroup analyses were performed, intra-aortic balloon pumping appeared slightly but not statistically significantly more beneficial than Impella devices. However, most notably in the aforementioned European multi-center study, 10 some evidence does suggest a specific benefit for LV unloading via the Impella family of devices.…”
Section: Discussionmentioning
confidence: 99%
“…Both adults and children have a 30‐day survival of 50%, despite markedly different scenarios. Adults without cardiac surgery (in the analysis by Hendrickson et al 12 ) and children with postcardiotomy shock (in the study by Sperotto et al 6 ) had similar poor outcomes. Furthermore, in children, there appears to be a dose‐dependent increase in adverse events with higher pump flow.…”
mentioning
confidence: 93%
“…In this issue of the Journal of the American Heart Association ( JAHA ), Hendrickson and colleagues 12 provide a valuable analysis to shed light on the debate over venting in VA‐ECLS. Using the Nationwide Inpatient Sample from 2016 to 2018, the authors identified 12 035 patients undergoing VA‐ECLS (3% of a total of 460 040 patients admitted with CS during this time period).…”
mentioning
confidence: 99%